Association between the thickness of the collagen in the amniotic membrane with the incidence of premature rupture of membranes - Marpaung, Johny (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Neonatal Mortality Rate in Indonesia is 19 deaths/1,000 live births and IMR is 32 deaths/1,000 live births which can be associated with the incidence of premature rupture of membranes (PROM). In America, PROM occurs in 2-3% of all pregnancies and 40% associated with preterm birth. Some studies indicate a difference in the thickness of the collagen in the membrane architecture cause structural abnormalities that occur in PROM. Methods: This study is an observational analytic study with cross sectional study design to see the difference in the thickness of the collagen membrane of the amnion PROM patients with normal pregnant patients conducted in the Department of Obstetrics and Gynecology, Faculty of Medicine USU-General Hospital of Adam Malik, and District Hospital USU on December 2014-March 2015. Sampling was carried out in the delivery room and operating room in General Hospital of Adam Malik. Data analysis was performed by univariate analysis to find the characteristics of the sample and bivariate analysis to compare the thickness of the collagen in amnion membranes at term PROM patients and normal pregnant. Results: This study showed the thickness of the collagen mother with PROM was 108.11±14.06 mm thinner than the average thickness of the collagen normal pregnant women which was 172.06±38.40 mm. And the thickness of amniotic mother with PROM was 522.72±85.63 mm thinner than the thickness of normal pregnant women amnion was 702.72±180.07 mm. Conclusions: Statistical test result with t-test. p value <0.05 showed a significant difference collagen thickness and amnion thickness at PROM group with normal pregnant group that showed an association with the PROM and collagen thickness.